Русские пословицы и поговорки - Соболев Анатолий Иванович (Сов. Россия, 1983)
Экземпляры: ЦРБ (20210503) / Инвентарный номер: 5420 / Сис.шифр: 82.3(2=Рус)-411 / Авт.знак: Р89 / ГРНТИ: 17 / ББК: 82.3(2=Рус)-411.06